(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Extracurricular activities are integrated. Reading in the classroom forms the reading skills required for STO, teaches students to understand the work they are reading, enriches their vocabulary. Extracurricular activities are fun and engaging activities that enrich children’s knowledge and provide material for comparison. This article discusses these